Radiographic Evaluation of Osteoporosis through Detection of Jaw Bone Changes: A Simplified Early Osteoporosis Detection Effort - Menik Priminiarti; Bramma Kiswanjaya; Hanna Bachtiar Iskandar (Makara Journal of Health Research, 2011)
Osteoporosis has become a worldwide problem and has been known as a silence disease. Nowadays, there are a lot of diagnostic tools for detecting osteoporosis. Eighty eight postmenopausal were included and underwent digital panoramic, digital periapical, and conventional radiography. Ultrasound bone densitometry of os calcis used as gold standard. Correlation between stiffness index (SI) with a digital dental, digital panoramic and conventional dental radiography are 0.170 (p = 0.11), -0382 (p = 0.001) and 0.246 (p = 0.021) respectively. Significant relationship was found between the SI only with digital panoramic and conventional dental. The highest correlation was found between SI values with mandibular Inferior Cortex on digital panoramic (-0.382, Pearson Correlation Tests). Correlation between digital panoramic radiographs and the SI values was the highest of the three radiographic modalities in this study. This indicates that evaluation of cortical bone is more accurate than cancellous bone. Bone quality evaluation in patients at high risk for osteoporosis using panoramic and dental conventional radiograph by dentist, contributes in preventing further occurrence of osteoporosis which in turn could reduce mortality and morbidity of osteoporosis in Indonesia.